Teaching Art Music in Nigerian Schools: The Academic, Technical and Social Implications - Femi Sinaola Abiodun (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2018)
Art music in the Nigerian context is the composition of Nigerians who have formal music training and have composed using Western medium to express traditional Nigerian music. This paper sets out to illuminate the technicalities involved in this form of musical composition and proposes a model of art music instruction for Nigerian schools. The author posits that the teaching and performing of art music in Nigerian schools will bring music closer to the people. He argues that whereas art music is an aberration from Nigerian traditional music, yet with concerted efforts and skill, the practice of art music will help in preserving Nigerian culture on paper and facilitate the promotion of its local music to the global level. The paper concludes that traditional music elements that are entrenched in art music composition can constitute a model and parameter for identifying and appreciating Nigerian music. The teaching of art music therefore must be encouraged by Nigerian music curricular planners. Art music in Nigerian context is the composition of Nigerians who have formal music training and have composed usingWestern medium to express traditional Nigerian music. This paper sets out to illuminate the technicalities involved in this form of musical composition and proposes a model of art music instruction for Nigerian schools. The author posits that the teaching and performing of art music in our schools will bring music closer to the people. The author equally argues that whereas art music is an aberration from our traditional music, yet with concerted efforts and skill, the practice of art music will help in preserving our culture on paper and facilitate the promotion of our local music to the global level. The paper concludes that traditional music elements that are entrenched in art music composition can constitute a model and parameter for identifying and appreciating Nigerian music. The teaching of art music, therefore, must be encouraged by Nigerian music curricular planners.